Laser Communications for Satellite-Terrestrial Integration: Research Status, Key Technologies, and Future Prospects - YUAN Renzhi; GUO Jia; YAO Haifeng; CHEN Zhibei; LI Yuchai; SUN Yaohua; PENG Mugen (天地一体化信息网络)
Satellite laser communication uses laser with shorter wavelength as the information carrier for data transmission, which can achieve a higher data transmission rate than RF communication. With an abundant spectrum resource of in optical band, the laser communication has a larger bandwidth than RF communication. Besides, because of the highly directional and narrow beam characteristics of the laser beam, it is difficult to intercept and eavesdrop the laser links. Satellite laser communication, with its characteristics of high speed, high bandwidth, high security, and abundant spectrum resources, has become an important supporting technology for the development of future 6G satellite-terrestrial integration networks. This paper summarized the current research status of laser communication for satellite-terrestrial integration both domestically and internationally, with a focus on key technologies such as satellite laser communication pointing, acquisition, and tracking, modulation and coding, switching and routing, and laser-radio frequency cooperation. The future development directions of corresponding key technologies were also discussed, provided direction reference for future research and development of laser communication technology for satellite-terrestrial integration networks in China.